Etnolinguistik Terhadap Konflik Budaya Dalam Interaksi Bahasa di Drama Korea Pyramid Game - Seftia Wulan Ayu Ningrum; Taswirul Afkar; Salsa Devista Mayangsari (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study examines cultural conflict in language interaction within the Korean drama Pyramid Game through an ethnolinguistic approach. The main focus of the research is to analyze how language is used as a tool of power, domination, and resistance within the socially hierarchical context of a school setting. Data is derived from the dialogues and actions of key characters such as Baek Ha Rin, Sung Soo Ji, and Seo Do Ah, which reflect power dynamics and efforts to resist oppressive systems. The analysis reveals that language functions not only as a means of communication but also as an instrument for asserting authority and mobilizing solidarity. Baek Ha Rin employs intimidating speech to maintain her position at the top of the social pyramid, while Sung Soo Ji uses language to build a collective movement against injustice. The drama also illustrates symbolic violence through nonverbal communication forms such as exclusion and social gestures. These findings affirm that language in Pyramid Game reflects cultural conflict embedded within an unequal social system and has the potential to generate real-world impacts on society.